2014
DOI: 10.3329/pa.v24i1-2.19171
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs of the Fish Farmers on Integrated Fish Farming

Abstract: The study was carried out to determine the extent of training needs of the fish farmers on integrated fish farming and to explore the relationship between the selected characteristics of the fish farmers and their extent of training needs on integrated fish farming (IFF). Four villages, namely North Gouari, South Gouari, Rajpur and Satrasia under Muktagacha Upazila (sub-district) of Mymensingh district were the locale of the study. Ninety fish farmers (out of the total of 300) were randomly selected as a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hossain [20] found that "the majority (about 82%) of the potato farmers had medium to high training need in his study area". Yeasmin et al [21] reported that "almost 99% of fish farmers had medium to high training need in their study area". The pineapple growers in the study area could not perform their jobs properly due to a lack of knowledge, education, communication exposure, etc.…”
Section: Overall Training Need Of the Pineapple Growersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hossain [20] found that "the majority (about 82%) of the potato farmers had medium to high training need in his study area". Yeasmin et al [21] reported that "almost 99% of fish farmers had medium to high training need in their study area". The pineapple growers in the study area could not perform their jobs properly due to a lack of knowledge, education, communication exposure, etc.…”
Section: Overall Training Need Of the Pineapple Growersmentioning
confidence: 99%
“…Olorunfemi et al [29] revealed that the age of the fish farmers had a significant relationship with their training need on value-addition initiatives. Yeasmin [21] found a negative relationship between age and the training need of fish farmers in integrated fish farming. Education of the pineapple growers had a negative and significant relationship with their training needs.…”
Section: Relationship Between the Selected Characteristics Of The Pin...mentioning
confidence: 99%
“…Social mobility of the farmers had a significant negative impact on the training need of the Tilapia Farmers, indicating that with a one unit increase in social mobility, farmers' training needs decreased by 0.299. This is due to the fact that the mobility of fish farmers may alter their attitude toward the adoption of better farming techniques (Yeasmin et al, 2014).…”
Section: Social Mobilitymentioning
confidence: 99%
“…However, fish production has been facing plenty of problems like poor knowledge, poor skills, high cost of inputs, increased feed cost, improper management practices, poor communication facilities, high labor cost etc. that may create obstacles to maximizing productivity (Ahmed, 2005;Yeasmin et al, 2014;Hossen, 2016). On the other hand, technology in fish and seeds production culture has been upgrading daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation